PERJANJIAN PERDAGANGAN DAN EKONOMI IEU-CEPA: KERANGKA WAKTU RATIFIKASI DAN IMPLIKASINYA BAGI AKSES PASAR DAN KERJA SAMA EKONOMI STRATEGIS INDONESIA DAN UNI EROPA DI TENGAH DINAMIKA GLOBAL - Novita Triyatun (CV. ADIBA AISHA AMIRA, 2025)
This study analyses the ratification timeline of the Indonesia–European Union Trade and Economic Agreement (IEU-CEPA) and its implications for market access and strategic economic cooperation between the two parties amid global geopolitical and economic dynamics. The complex and time-consuming ratification process has led to regulatory uncertainty and market access barriers, which could potentially reduce the competitiveness of Indonesian exports compared to other countries that have already concluded similar agreements with the European Union. In addition, the IEU-CEPA offers strategic opportunities in strengthening the green economy sector, digitalisation, supply chains, and human resource capacity building, which are key to navigating global economic and geopolitical shifts. Through descriptive qualitative methods and content analysis of the agreement documents, as well as comparative studies with similar trade agreements in the Southeast Asian region, this study provides important recommendations regarding the acceleration of ratification and regulatory harmonisation to maximise the benefits of trade and economic diplomacy. The results of this study are expected to serve as a reference for policymakers in optimising Indonesia's role in an increasingly competitive and sustainable international trade arena.